Статистична оцінка демографічних змін і трудового потенціалу України - Паянок, Тетяна Миколаївна; Яковенко, Дмитро Сергійович; Остапенко, Яна Олександрівна; Паянок, Тетяна (КНДУ «Науково-дослідний інститут соціально-економічного розвитку міста», 2025)
У статті досліджено сучасні тенденції демографічного розвитку України, зокрема скорочення чисельності населення, старіння нації, зниження народжуваності та посилення міграційних процесів. На основі статистичного аналізу встановлено, що щорічне скорочення населення становить у середньому 379,5 тис. осіб. Виокремлено основні причини демографічної кризи – високий рівень смертності, трудову міграцію, соціально-економічну нестабільність і наслідки воєнних дій. Доведено, що війна суттєво трансформувала демографічну поведінку населення, зумовивши поглиблення дефіциту трудових ресурсів. У роботі підкреслено необхідність комплексної державної політики, спрямованої на збереження людського капіталу, стимулювання народжуваності та підтримку соціально-економічної стабільності для забезпечення демографічної стійкості країни.

The article highlights the relevance of studying Ukraine’s demographic crisis as a critical challenge to the country’s social and economic security. In recent years, Ukraine has faced an accelerated population decline, a rapid aging process, and growing migration flows, which together undermine the state’s labor potential and long-term development capacity. The full-scale Russian invasion has intensified these negative trends, transforming migration behavior, family formation patterns, and labor market participation. The purpose of this study is to analyze the current demographic situation in Ukraine, identify the main causes and consequences of population decline, and determine the impact of demographic changes on the formation and realization of the country’s labor potential. The research applies comparative, statistical, and analytical methods to evaluate demographic indicators and labor market dynamics. The study also uses a structural-functional approach to reveal interconnections between population reproduction, employment levels, and human capital sustainability. A review of current scientific publications and official statistical data complements the empirical base. The study establishes that the population of Ukraine decreases annually by an average of 379.5 thousand people, driven primarily by high mortality rates, low fertility, large-scale external migration, and the effects of war. The demographic burden on the working-age population continues to rise, particularly in rural areas and regions most affected by hostilities. The war has deepened regional disparities and caused significant outflow of qualified labor, resulting in a shortage of skilled workers. The analysis confirms that demographic deterioration directly threatens the country’s labor potential and socioeconomic stability. To overcome the demographic crisis, Ukraine needs a comprehensive policy aimed at preserving and restoring human capital. Priority measures should include stimulating birth rates through social incentives, encouraging the return of migrants, developing regional employment programs, and strengthening educational and health systems. Ensuring demographic sustainability is essential for Ukraine’s post-war recovery, national resilience, and long-term competitiveness.
Keywords: демографічна криза; трудовий потенціал; міграційні процеси; старіння населення; статистичний аналіз; відтворення населення; demographic crisis; labor potential; migration processes; population aging; statistical analysis; population reproduction